The effect of Gallium Aluminium Arsenide laser on fibroblast activity: An in vitro dosimetry study - Susan Mars; Anil Chuturgoon; Dhamarai Pillay; Maurice Mars (AOSIS, 1998)
The effect of different doses of low intensity laser therapy (L.I.L.T.) on human fibroblasts was investigated to determine the optimal dose required to stimulate fibroblast proliferation. Human fibroblasts were cultured in vitro and irradiated with different energy densities of 83Onm continuous output infra-red laser using a Gallium Aluminium Arsenide laser. The fibroblasts were irradiated on three consecutive days at energy densities, ranging from 0.2 to 5 J.cm2, delivered at an average radiant power of 30 mW, and at a constant distance of lcm from the fibroblasts. Fibroblast activity was assessed on the fourth day using a calorimetric MTT (tetrazolium) cleavage assay. There was a significant increase in fibroblast proliferation at laser treatment energy densities of 0.4 J.cm2 and 5 J.cm2. Difficulties associated with in vivo and in vitro studies of the effect of laser treatment are discussed.